A new family of Triassic planthoppers (Hemiptera: Fulgoromorpha: Fulgoroidea) from the Shaanxi Province of China. Issue 1 (2nd January 2021) - Zhang, Qianqi; Jiang, Tian; Szwedo, Jacek; Zhang, Haichun
Abstract: A new family of planthoppers, Szeiiniidae fam. nov., is described on the basis of a well-preserved forewing from the Upper Triassic Yanchang Formation of Huanglong County, Shaanxi Province, China. As the only specimen of the new family, Szeiinia huanglongensis gen. et sp. nov. differs from other families within Fulgoroidea by a unique combination of venation characters, and most significantly, the early branching of the MP vein, and low length/width ratio of the forewing. Our finding adds to the current understanding of morphological variability amongst planthoppers, and confirms high levels of diversity within Fulgoroidea at an early stage of the Mesozoic. Qianqi Zhang [qianqizhang@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China, and University of Chinese Academy of Sciences, Beijing 100049, PR China; Tian Jiang [jiangtian@cugb.edu.cn ], State Key Laboratory of Biogeology and Environmental Geology, China University of Geosciences, No. 29, Xueyuan Road, Haidian District, Beijing 10083, PR China; Jacek Szwedo [jacek.szwedo@biol.ug.edu.pl ], Laboratory of Evolutionary Entomology and Museum of Amber Inclusion, Department of Invertebrate Zoology and Parasitology, University of Gdańsk, 59, Wita Stwosza Street, PL80-308 Gdańsk, Poland; and Haichun Zhang* [hczhang@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China.